The effectiveness of lifetime use of cows depending on genotypic factors - Скляренко, Ю. І. (Scientific Progress & Innovations, 2018)
The article presents the main results of research on determining the influence of genotype factors on indicators of lifetime use of cows. Domestic scientists pay much attention to the study of the influence of genotype factors on indicators of lifetime use of cows. The study was conducted according to the materials of the primary breeding records in the herd of State Enterprise «Experimental Farm of Institute of Agriculture of Northern East of NAAS» of Sumy region – it is one of the leading breeding factories of Ukrainian brown dairy breed cattle breeding. The materials of the electronic information database in SUMS ORSEC format are used as of 2017. In result of the conducted researches we have found that in animals of Ukrainian brown dairy breed worse indicators of lifetime productivity and duration of economic use. The coefficients of inheritance («daughter–mother») of indicators of lifetime use of Ukrainian brown dairy breed cows are low and in most cases statistically unreliable. Inheritance of life expectancy of cows is low h2=0,09; duration of economic use – h2=0,12; the duration of the lactation period – h2=0.08. Even lower the value of the coefficient of inheritance is characterized by the value of lifetime milk yield h2=0,07; milk yield per 1 day of life h2=0,02. We established in the course of studies coefficients of inheritance and the power of influence on the indicators of lifetime use of cows by the method of «father–daughter» in the context of large-scale breeding of dairy cattle give reason to expect high efficiency of selection with intensive use of bulls- producers on the grounds of lifetime use of cows in comparison with the method of «mother–daughter». The impact of origin for the father on the indicators of lifetime use is 20.5–33.4 %.